Study protocol: a randomised controlled trial of cognitive remediation for a national cohort of forensic mental health patients with schizophrenia or schizoaffective disorder. Issue 1 (December 2016) - O'Reilly, Ken; Donohoe, Gary; O'Sullivan, Danny; Coyle, Ciaran; Mullaney, Ronan; O'Connell, Paul; Maddock, Catherine; Nulty, Andrea; O'Flynn, Padraic; O'Connell, Carina; Kennedy, Harry
Abstract Background Evidence is accumulating that cognitive remediation therapy (CRT) is an effective intervention for patients with schizophrenia or schizoaffective disorder. To date there has been no randomised controlled trial (RCT) cohort study of cognitive remediation within a forensic hospital. The goal of this study is to examine the effectiveness of a trial of cognitive remediation for forensic mental health patients with schizophrenia or schizoaffective disorder. Methods An estimated sixty patients will be enrolled in the study. Participants will be randomised to one of two conditions: CRT with treatment as usual (TAU), or TAU. CRT will consist of 42 individual sessions and 14 group sessions. The primary outcome measure for this study is change in cognitive functioning using the MATRICS Consensus Cognitive Battery (MCCB). Secondary outcomes include change in social and occupational functioning, disorganised symptoms, negative symptoms, violence, participation in psychosocial treatment and recovery. In addition to these effectiveness measures, we will examine patient satisfaction. Discussion Cognitive difficulties experienced by schizophrenia spectrum patients are associated with general functioning, ability to benefit from psychosocial interventions and quality of life. Research into the treatment of cognitive difficulties within a forensic setting is therefore an important priority. The results of the proposed study will help answer the question whether cognitive remediation improves functional outcomes in forensic mental health patients with schizophrenia or schizoaffective disorder. Forensic mental health patients are detained for the dual purpose of receiving treatment and for public protection. There can be conflict between these two roles perhaps causing forensic services to have an increased length of stay compared to general psychiatric admissions. Ultimately a focus on emphasising cognition and general functioning over symptoms may decrease tension between the core responsibilities of forensic mental health services. Trial Registration ClinicalTrials.gov Identifier:NCT02360813 . Trial registered Feb 4th 2015 and last updated May 1st 2015.